Nontuberculous Mycobacteria in Cystic Fibrosis - Richards, Christopher J.; Olivier, Kenneth N. (Seminars in Respiratory and Critical Care Medicine, 2019)
Over the past decade, the incidence of nontuberculous mycobacterial (NTM) infection has been increasing in cystic fibrosis patients. Along with this have come a host of complications and burdens to patients that threaten longevity and quality of life. The two main constituents of NTM pulmonary disease, Mycobacterium avium complex (MAC) and M. abscessus, are notoriously difficult to treat with suboptimal clinical responses and are accompanied by high treatment burdens for patients. This review aims to summarize the current knowledge of NTM epidemiology, pathogenesis, professional society guidelines for diagnosis and treatment, and the efficacy of current management recommendations, with attention to cystic fibrosis patients. We go on to examine drugs of emerging but unknown efficacy in clinical use to provide a comprehensive assessment of the current state of management of NTM for cystic fibrosis patients.
Keywords: cystic fibrosis; nontuberculous mycobacterium; Mycobacterium avium complex; Mycobacterium abscessus; clofazimine; bedaquiline; liposomal amikacin